The impact of positive psychological capital, problem solving ability and clinical competence on career adaptability in nursing students - Shin, Eun Hee; Lee, Hyea Kyung (Edelweiss Applied Science and Technology, 2024)
The purpose of this study is to identify the factors affecting career adaptability in nursing students, focusing on positive psychological capital, problem-solving ability, and clinical competence. The study participants were fourth-year nursing students from one university in Chungbuk and one university in Gyeongbuk, with 151 questionnaires analyzed. The results indicated that positive psychological capital (β=.87, p<.001) was the significant factor affecting career adaptability (F=197.050, p<.001), explaining 78.6% of the variance. Based on these findings, it is recommended to use this study as foundational data for developing nursing education programs to enhance career adaptability in nursing students.